Sodium butyrate regulates macrophage polarization by TGR5/β-arrestin2 in vitro - Miao Liu; Wen-jie Xie; Xu Zhang; Wei Wu; Guang Li; Lu Wang (Molecular Medicine)
Abstract Background Macrophages play an important role in the pathogenesis of ulcerative colitis (UC). We will explore the effects of sodium butyrate (SB) on macrophage function. Methods The targets of butyric acid were identified using SwissTargetPrediction database and surface plasmon resonance (SPR). Limited proteolysis mass spectrometry (Lip-MS) was used to further investigate the binding sites of butyric acid with its targets and molecular docking was employed to simulate their binding modes. Macrophage polarization model was established with lipopolysaccharide (LPS) in vitro. Takeda G protein-coupled receptor 5 (TGR5) and β-arrestin2 expression and macrophage polarization markers were detected with or without SB. Results TGR5 was identified as the target of butyric acid. Moreover, the amino acid regions 275–286 and 321–330 of TGR5 (GPBAR1 [275–286] and GPBAR1 [321–330]) were the potential binding regions for butyric acid. Based on molecular docking analysis, butyric acid formed effective hydrogen-bonding interactions with ASP-284 and TYR-287 of TGR5. In cell experiments, LPS inhibited the expression of TGR5, β-arrestin2, IL-10, ARG1, and CD206 and increased the expression of IL-1β, iNOS, and CD86, while SB reversed the effect of LPS. SBI-115, a TGR5 antagonist, and knockdown of β-arrestin2 inhibited the effect of sodium butyrate. INT-777, a TGR5 agonist, reversed the inhibitory effect of knockdown of β-arrestin2. Conclusion SB inhibited M1-like polarization and promoted M2-like polarization induced by LPS via TGR5/β-arrestin2 in RAW264.7 cells and TGR5 was the target of SB.